Table of content and Editorial - Dinbabo, Mulugeta (African Human Mobility Review, 2021)
This issue consists of six articles. The first article by Ajwangâ€™ Warria entitled â€œStateless transnational migrant children in South Africa: Implications and opportunities for social work interventionâ€, examines statelessness in South African migrant children and conducts a literature review to clarify the phenomenon. This research assesses the causes and circumstances that lead to statelessness among South African migrant children. The findings indicate that a large number of migrant children are at risk of statelessness in South Africa. This research contributes to the literature and debates on statelessness in childhood and highlights the potential role of social workers in addressing this important phenomenon. In general, this is South Africa’s first research on statelessness from a social work perspective and shows how transnational migration and national legislation can contribute to statelessness and put children at risk.